2014
DOI: 10.14814/phy2.12207
|View full text |Cite
|
Sign up to set email alerts
|

NK1-receptor-expressing paraventricular nucleus neurones modulate daily variation in heart rate and stress-induced changes in heart rate variability

Abstract: The paraventricular nucleus of the hypothalamus (PVN) is an established center of cardiovascular control, receiving projections from other nuclei of the hypothalamus such as the dorsomedial hypothalamus and the suprachiasmatic nucleus. The PVN contains a population of “pre‐autonomic neurones” which project to the intermediolateralis of the spinal cord and increase sympathetic activity, blood pressure, and heart rate. These spinally projecting neurones express a number of membrane receptors including GABA and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 49 publications
0
13
0
Order By: Relevance
“…Neurons within the paraventricular nucleus express NK-1R which modulate stress induced changes in heart rate [33]. In our studies, treatment with the NK-1RA did not alter the heart rate (Fig 6C).…”
Section: Resultsmentioning
confidence: 43%
“…Neurons within the paraventricular nucleus express NK-1R which modulate stress induced changes in heart rate [33]. In our studies, treatment with the NK-1RA did not alter the heart rate (Fig 6C).…”
Section: Resultsmentioning
confidence: 43%
“…It was also not feasible with the methodology used in the present study to obtain reasonable values for the time between heart beats in order to deduce HR variability (HRV) in the AGRs. The HRV parameter, which is often used to complement HR as an indicator of autonomic activity (Acharya et al 2006), was shown in some rodents to be significantly increased/higher (lower sympathetic/ higher parasympathetic activity) during summer (Weil et al 2009), in females (Johnson et al 2011), during the "inactive period" of the day (Albarwani et al 2013), and with mild psychological stress (Feetham and Barrett-Jolley 2014). It is conceivable that the HRV in AGRs may be elevated/higher during the rainy season, in does, during the afternoon (since AGRs are nocturnal), and in freemoving, unrestrained rats.…”
Section: Heat Index (°C)mentioning
confidence: 99%
“…The HR, which is an indicator of cardiovascular activity, is defined as the rate of heart beat, expressed in beats per minute (bpm). Although the paraventricular nucleus in the hypothalamus is an established center of cardiovascular control in rats (Feetham and Barrett‐Jolley ), the HR may be altered rapidly due to inputs from environmental cues (zeitgebers), such as ambient temperature and photoperiod, psychosocial factors like housing, or due to intense activity, including feeding, by the animal (van den Buuse ; Swoap et al. ; Azar et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In simplified form, non-circadian physiological effects of light on the autonomic regulation of heart rate realized through polysynaptic excitation glutamate-ergic projection from the retina to (1) the "pre-autonomic" [7] hypothalamic neurons that affect the autonomic centers of the brain stem and spinal cord, as well as (2) neuroendocrine hypothalamic centers responsible for the hormones secretion [5]. The first pathway is associated with projections from the suprahiazmatic nucleus to the parvocellular GABA-ergic neurons of paraventricular nucleus in hypothalamus.…”
Section: Introductionmentioning
confidence: 99%